A biomass small-scale externally fired combined cycle plant for heat and power generation in rural communities. (March 2019) - Amirante, Riccardo; Bruno, Sergio; Distaso, Elia; La Scala, Massimo; Tamburrano, Paolo
Highlights: Rural electrification needs technological solutions that are efficient, accessible, affordable, flexible, and sustainable. A low-cost plant that produces power and heat in small-scale through an externally fired biomass combine cycle was proposed. A prototype is under construction at LabZERO (Politecnico di Bari) to burn gas and solid biomass from agricultural waste. Energetic performances are comparable to the state-of-the-art for small-scale biomass plants. Expected levelized cost of energy is contained thanks to the low expected capital and marginal costs . Abstract : The authors propose a novel small-scale power plant capable of generating electricity and thermal energy from both solid and gaseous biomass, to be employed in rural electrification projects. The proposed system is based on mature and cheap technology, derived from the automotive sector, ensuring very low capital costs and minimum maintenance. The presence of an externally fired gas turbine permits to achieve great fuel flexibility and avoid possible problems of fuel supply in remote and isolated rural communities. The proposed solution makes rural communities capable of achieving energy autonomy targets, following a circular economy paradigm. Three possible configurations have been studied with a thermodynamic analysis in order to estimate system efficiency. Thanks to the reduced fixed and variable costs, the system allows to achieve performances comparable with those of other state-of-the-art technologies usually adopted for rural electrification. A prototype of the proposed system is developed at Politecnico di Bari (LabZERO).